Aplikasi Pupuk Hayati Terhadap Pertumbuhan dan Hasil Tanaman Cabe Keriting di Lahan Rawa Lebak - Mahdiannoor Mahdiannoor (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
Curly chilli are versatile plants, mainly used as household consumption such as herbs but can also be used in the food processing industry. Lebak wetland nature and character similar to acid sulfate soil that affects the physical, chemical and biological soil, to solving issues specifically to support the cultivation of curly chilli, one attempts to do is to provide input inorganic materials. This study aims to (i) know the biofertilizer, and (ii) get the best dosage application the biofertilizer to the growth and yield of curly chilli on lebak wetlands. This research was held at Pasar Senin Village, Amuntai Tengah District, Hulu Sungai Utara Regency from May to August 2012. This research used Randomized Block Design (RBD), with 5 treatments and 5 replicates, so get 25 units of exspriment. Factor test is biofertilizers, which are: t0 = 0 cc 1-1, 1-1 cc t1 = 1, t2 = 2 cc 1-1, 1-1 cc t3 = 3, t4 = 4 cc 1-1 . The results of this study indicate that biofertilizer treatment highly significant for all variables are observed, namely plant height, total of productive branches, fruit weight and total of fruit crops. Biofertilizer treatment 4 cc.l-1is the best treatment for all variables.